JURIDICAL STUDY OF THE MANAGEMENT OF SELAPARANG FORMER AIRPORT BY PT. ANGKASA PURA I - Fransiska Lidya Rusphitawati (Fakultas Hukum Universitas Mataram, 2013)
This research aimed to study or analyze the state capital participation in PT. Angkasa Pura as a legal body (Company of the state/ BUMN) based on the positive law of Indonesia, to study and analyze the legal status of the former Selaparang Airport which managed out of its function and to study and analyze the assets hand over of former Selaparang airport which managed out of its function. This thesis occupied the juridical-normative and juridical-empiric research method. From several problem formulations concerning the management of the former Selaparang airport writer concludes that the capital participation on PT. Angkasa Pura as the company of the state (BUMN) based on Indonesia’s positive law particularly laid on the regulation of the government of the Republic of Indonesia number 38 of 1999 concerning addition on the state of Indonesia capital participation into the share of the state limited company (PERSERO) PT Angkasa Pura I and the regulation of the government number 19 of 2002 concerning addition on the state of Indonesia capital participation into the share of the state limited company (PERSERO) PT Angkasa Pura I. Legal status of the former Selaparang airport is still under the occupation of the transportation department which managed by PT Angkasa Pura I. The assets hand over of PT Angkasa Pura I is regulated in the regulation of the government number 38 of 2008 concerning management of property of the state/region. In fact in the management of the former Selaparang airport by PT Angkasa Pura I there is no assets hand over have been done.Keywords: Management, Former Selaparang Airport